Supervisory overload and its impact on postgraduate student success: A cross-sectional case study of selected institutions. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background This study examines the extent of supervisory overload and its impact on the academic experiences and completion outcomes of postgraduate students across selected South African universities. Methods A cross-sectional qualitative case study design was used. The study was conducted at two South African universities between February and April 2025. A purposive sample of 30 participants was selected: 20 master s-level postgraduate students (mean age: 28.4 years; 65% female) and 10 academic supervisors (mean age: 44.7 years; 60% male), all involved in research-based programs. Data were collected through semi-structured interviews exploring supervisory capacity, feedback practices, student satisfaction, and institutional support. Thematic analysis followed Braun and Clarke’s framework, with triangulation across participant groups to ensure credibility. Results Seventy percent of students reported inconsistent or delayed feedback, primarily due to supervisory overload linked to teaching, administrative duties, and excessive supervision assignments. Sixty percent of supervisors acknowledged supervising 10 to 15 students simultaneously, exceeding recommended levels. This overload diminished mentorship quality and led to feelings of neglect among students. Participants also reported reduced meeting frequency, delays in research approvals, and a lack of personalised academic engagement. Emotional stress and reduced motivation were frequently cited by students. Institutional mechanisms to monitor and manage supervisory loads were found to be weak or inconsistently enforced across faculties. Conclusion Supervisory overload negatively affects postgraduate success by limiting academic engagement and delaying research progression. Without effective workload management systems, supervisors remain overstretched, and students experience heightened frustration and academic delays. Recommendations Universities should adopt clear supervisory workload caps and implement structured support systems to ensure equitable supervision and improve postgraduate outcomes.